Development of a Knudsen arc with a cathode spot; Soviet Physics. Doklady; Vol. 33 - Koval N. N.; Kreindel Yu. E.; Litvinov E. A.; Mesyats G. A. Gennady Andreyevich; Tolkachev V. S.; Schanin P. I. (1988, 1988)
В фонде НТБ ТПУ отсутствует